RANCANG BANGUN DAN IMPLEMENTASI SISTEM INFORMASI TERINTEGRASI (INTEGRATED INFORMATION SYSTEM) E-GOVERNMENT BERBASIS OPEN SOURCE - Perdananugraha, Gonang May (LIPI Press, 2010)
Integrated information system of e-government (http://www.bit.lipi.go.id) which designed and built using Joomla 1.5 aims to raise the potential of information possessed by the Technical Implementation UniTechnology Information Division of LIPI, to be known and exploited by the public. This system also as a forum / medium for UPT-BIT civitas in communicating and exchanging information through the internet. Potential information which poured and integrated into such systems are the potential information of multimedia, the potential information for library, and the potential information for dissemination and collaboration. Joomla features that used in buil ding such systems are JoomlaComment!, Media Player, Agora Forum, DOCman, WbGallery, EventList, AllVideos Reloaded, etc.